2015
DOI: 10.1007/s10853-015-9502-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationship of recycled carbon fibres revealed by pyrolysis recycling process

Abstract: The structure-property relationship for recycled carbon fibres is investigated by characterisation of the structure changes induced by the pyrolysis recycling process. Two important factors influencing the properties of recycled carbon fibres are identified for various recycling processes: oxidative effect and thermal effect. The oxidative effect results in surface defects, and the surface defects causes a reduction in tensile strength and lateral crystallite size. The thermal effect of the recycling process r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The O/C ratio of the investigated fibres equalled 11.01%, whereas the O/C ratio of virgin fibres was 20%. This value is comparable to the results obtained by Jiang and Pickerling, where the O/C ratio for fibres after recycling was about 15% and before it 25% [20]. The results indicate that applied recycling process decreases the concentrations of oxygen in comparison with virgin carbon fibres.…”
Section: Surface Chemistrysupporting
confidence: 89%
See 2 more Smart Citations
“…The O/C ratio of the investigated fibres equalled 11.01%, whereas the O/C ratio of virgin fibres was 20%. This value is comparable to the results obtained by Jiang and Pickerling, where the O/C ratio for fibres after recycling was about 15% and before it 25% [20]. The results indicate that applied recycling process decreases the concentrations of oxygen in comparison with virgin carbon fibres.…”
Section: Surface Chemistrysupporting
confidence: 89%
“…The testing range was up to 5 nm deep into the carbon fibres and the percentages of carbon (C1s), oxygen (O1s), nitrogen (N1s), sulphur (S2p) and silicone (Si2p) were also taken into account [20][21][22][23]. The results are presented in the high-resolution XPS spectra ( Fig.…”
Section: Surface Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the use of alkali catalysts could decrease the tensile strength. Guozhan and Pickering [19] have shown that the effect of recycling process on recovered carbon fibers properties can be attributed to two factors: oxidative effect and thermal effect. In solvolysis process, only the thermal effect can be considered, while, in pyrolysis process followed by the char oxidation, both are involved.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the different fiber surface treatments result in a change of the fiber free surface energy as reflected by the change in contact angle. Jiang and Pickering [35] reported that the use of the Yamaki and Katayama criteria to study the structure-property relationships for recycled carbon fibers is able to detect changes of the contact angle resulting from the pyrolysis of the carbon fibers. From both, the contact angle and the concept of work of adhesion they estimated the surface free energy of the fibers.…”
Section: Contact Angle Between the Epoxy Resin And Surface Modified Fmentioning
confidence: 99%